A Nexus Between the Elements of Brand Equity and its Creation: Evidence from the Telecommunication Industry of Sri Lanka - Ismail , Mohamed; Hilal , Mujahid (Asian Journal of Empirical Research, 2019)
The study provides deeper understanding of the brand equity elements and its creation in the telecommunication industry in Sri Lanka. The main objective of the study was to examine how the image, awareness, and loyalty of the brand create brand equity in the telecommunication industry in Sri Lanka. A survey of 422 customers was conducted by a questionnaire. Multivariate analysis was applied using SPSS 20. The findings show that all variables included in this study support the creation of customer-based brand equity in the telecommunication sector in Sri Lanka. It was found that the telecommunication sector should focus more on generating brand knowledge.